Algicidal agent and algicidal method
Titanium oxide particles with copper as a solid solution, optionally with tin or zinc, improve algae-proofing and transparency, addressing the limitations of conventional photocatalysts for building materials.
Patent Information
- Application Number
- JP2023112955
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-10
- Publication Date
- 2025-01-23
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Conventional photocatalyst compositions for algae prevention on building materials suffer from low transparency, insufficient photocatalytic function, and inadequate algae-proofing properties, especially in areas with limited sunlight exposure.
Development of titanium oxide particles with copper dissolved as a solid solution, combined with optional tin or zinc, to enhance algae-proofing properties and maintain transparency, applied as an algaecide in an aqueous dispersion medium.
The algaecide exhibits superior algae-proofing properties and transparency when irradiated with ultraviolet light, suitable for building materials without impairing design aesthetics.
Smart Images

Figure 2025010766000001 
Figure 2025010766000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an anti-algae agent and an anti-algae method. [Background technology]
[0002] In recent years, there has been a growing tendency among consumers to seek a hygienic living environment, and interest in daily necessities that have been treated to maintain cleanliness, such as with anti-fouling, anti-bacterial, anti-fungal, anti-viral and anti-odor properties.
[0003] Photocatalytic materials have attracted attention because they are widely effective in cleaning the surface of substrates, providing antibacterial, antifungal, antiviral, deodorizing, and antifouling properties through the photocatalytic reaction and photoinduced superhydrophilic phenomenon that occur when exposed to light such as sunlight or artificial lighting. Photocatalytic reaction refers to a reaction caused by excited electrons and holes generated by the absorption of light by a photocatalyst such as titanium oxide. The excited electrons and holes generated on the titanium oxide surface by the photocatalytic reaction cause an oxidation-reduction reaction with oxygen and water adsorbed on the titanium oxide surface to generate active species. Organic microorganisms, viruses, odors, dirt, etc. are decomposed by these active species, so it is believed that the above-mentioned cleaning effect of the substrate surface can be obtained.
[0004] The active species produced by photocatalytic reactions basically act on any type of organic matter, so photocatalysis is effective against a wide variety of microorganisms, viruses, odors, dirt, etc., and it hardly deteriorates over time. These are some of the advantages of photocatalysis.
[0005] The photoinduced superhydrophilic phenomenon of photocatalysis refers to a phenomenon in which the surface of a photocatalyst, typically titanium oxide, becomes more compatible with water as a result of absorbing light. The superhydrophilic phenomenon makes it easier to wash away dirt on the surface with water, so that even dirt made of inorganic substances that cannot be decomposed by photocatalytic reactions can be removed by simple washing with water. By utilizing this phenomenon, for example, dirt on the surface of an exterior material can be washed away with rainwater during rainy weather, making it possible to maintain a clean state for a long period of time without special maintenance. Exterior materials having such photocatalysts on their surfaces have been widely put to practical use as self-cleaning building materials.
[0006] Algae grow on building exterior materials such as tiles, concrete, and bricks, and depending on the environment, they can grow in large quantities and cause damage to the building's appearance. The environmental factors necessary for algae growth are water, light, heat, and air, but the presence of organic nutrients dramatically promotes their growth. Algae are microorganisms that contain chlorophyll, and can synthesize organic nutrients themselves through photosynthesis. Various anti-algae materials are being investigated to suppress the growth of algae on exterior materials, and photocatalysts are also being considered for use in anti-algae building materials, with the expectation that they will have an inhibitory effect on algae growth by decomposing algae and organic nutrients, taking advantage of the organic matter decomposition performance of photocatalytic reactions, and a self-cleaning effect that takes advantage of the photoinduced superhydrophilic phenomenon.
[0007] However, in places where sunlight is insufficient, such as the exterior wall on the north side of a building, or an exterior wall that is adjacent to a building, tree, or planting that blocks sunlight, the photocatalyst's function cannot be fully exerted and it cannot keep up with the rate of algae growth, so the anti-algae effect may not be achieved.
[0008] Therefore, it is being considered to use photocatalysts and anti-algae agents in combination to complement the anti-algae performance in places where there is insufficient sunlight.
[0009] For example, Patent Document 1 discloses that a coating film obtained from a photocatalytic composition containing an antibacterial metal compound such as copper, silver, gold, platinum, or zinc, a photocatalytically active inorganic compound such as titanium oxide, and a photocatalytically inactive inorganic compound such as silicon dioxide has excellent long-lasting anti-algae properties.
[0010] Patent Document 2 discloses that a photocatalyst material having a photocatalyst layer including photocatalyst particles such as titanium oxide, copper compound particles including a divalent copper ion compound, inorganic particles having no photocatalytic activity, and a binder has high antimicrobial properties, and in particular exhibits anti-algae properties for a long period of time. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] JP 2018-144003 A [Patent Document 2] JP 2018-095797 A Summary of the Invention [Problem to be solved by the invention]
[0012] The photocatalyst composition of Patent Document 1 uses a photocatalyst that suppresses the amount of active species such as hydrogen peroxide and hydroxyl radicals generated by photocatalytic reactions in order to prevent damage to the base coating film, so there are problems with the resulting coating film having low photocatalytic function and low transparency due to the large particle diameters of the photocatalyst and antibacterial compound used and their poor dispersibility. Furthermore, the photocatalyst particles contained in the photocatalyst material of Patent Document 2 have a large particle diameter, which causes a problem of low transparency of the coating film. Furthermore, even these photocatalysts with enhanced anti-algae functions still do not have sufficient performance, and there is still room for improvement. Therefore, the present invention aims to provide an anti-algae agent containing titanium oxide that can exhibit higher anti-algae properties than conventional agents, has high transparency, and does not impair the design when applied, for example, to building exterior materials, and an anti-algae method using said anti-algae agent. [Means for solving the problem]
[0013] In order to achieve the above-mentioned object, the inventors conducted detailed studies on the selection of titanium oxide, its combinations and quantitative ratios, combinations of titanium oxide with various materials, their quantitative ratios, and combination methods, and as a result, they discovered that titanium oxide with copper dissolved therein exhibits significantly higher anti-algae properties than conventional materials, particularly when irradiated with light including ultraviolet rays (wavelength 10 to 400 nm), which led to the creation of the present invention. This high anti-algae effect was not observed in copper alone, titanium oxide particles alone, or in simple mixtures of copper and titanium oxide particles where copper is present outside the titanium oxide particles, or in copper-loaded titanium oxide particles.It was found that this is an inherent property of titanium oxide particles with copper dissolved therein, in which copper is present inside the titanium oxide particle crystals.
[0014] Therefore, the present invention provides the following algae control agents, etc. [1] An anti-algae agent containing titanium oxide particles having copper dissolved therein. [2] The algae control agent according to [1], further comprising titanium oxide particles in which copper is not dissolved. [3] An anti-algae agent in which titanium oxide particles having copper dissolved therein are dispersed in an aqueous dispersion medium. [4] The algae-preventing agent according to [3], further comprising titanium oxide particles not having copper dissolved therein dispersed in an aqueous dispersion medium. [5] The anti-algae agent according to [3] or [4], wherein the dispersed particle size of the titanium oxide particles having copper dissolved therein is 5 to 50 nm in terms of volume-based 50% cumulative distribution size and 5 to 150 nm in terms of 90% cumulative distribution size, as measured by a dynamic scattering method using laser light. [6] The anti-algae agent according to any one of [1] to [5], wherein the amount of copper dissolved in the titanium oxide particles is 2 to 200 in terms of a molar ratio to titanium (Ti / Cu). [7] A step of applying the anti-algae agent according to any one of [3] to [6] to a surface of a member; and A process for drying the surface of components The method for preventing algae on a surface of a member comprises the steps of: [8] The method for preventing algae on a surface of a component according to [7], further comprising a step of irradiating the surface of the component with ultraviolet light after the step of drying the surface of the component. Effect of the Invention
[0015] The anti-algae agent of the present invention exhibits higher anti-algae properties than conventional agents, particularly when irradiated with light including ultraviolet rays (wavelength 10 to 400 nm), and can easily produce a highly transparent photocatalyst film. Therefore, the anti-algae agent of the present invention is useful for imparting anti-algae properties to the surfaces of various types of exterior materials and other components without impairing their design. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The anti-algae agent of the present invention will be described in detail below.
[0017] <Titanium oxide with copper dissolved in it> The anti-algae agent of the present invention contains titanium oxide particles having copper dissolved therein.
[0018] Generally, three types of crystalline phases of titanium oxide particles are known: rutile type, anatase type, and brookite type, but the crystalline phase of titanium oxide particles in which copper is dissolved is preferably mainly anatase type. Note that "mainly" here means that titanium oxide particles of this crystalline phase are contained in 50% by mass or more of the entire titanium oxide particles, preferably 70% by mass or more, more preferably 90% by mass or more, and may be 100% by mass.
[0019] In this specification, the term "solid solution" refers to a phase in which atoms at the lattice points of a certain crystal phase are replaced by other atoms, or other atoms enter the lattice gaps, i.e., a mixed phase in which another substance is considered to have been dissolved in a certain crystal phase, and refers to a homogeneous crystal phase. A solid solution in which solvent atoms at the lattice points are replaced by solute atoms is called a substitutional solid solution, and a solid solution in which solute atoms enter the lattice gaps is called an interstitial solid solution, and both are referred to in this specification.
[0020] The titanium oxide particles in which copper is dissolved, which is contained in the anti-algae agent, form a solid solution with copper. The solid solution may be of the substitutional type or the interstitial type. A substitutional solid solution of titanium oxide is formed when the titanium sites of titanium oxide crystals are substituted with various metal atoms, and an interstitial solid solution of titanium oxide is formed when various metal atoms enter the lattice gaps of titanium oxide crystals. When various metal atoms are dissolved in titanium oxide, only the peak of the crystalline phase of titanium oxide is observed when the crystalline phase is measured by X-ray diffraction or the like, and the peak of the compound derived from the various metal atoms added is not observed.
[0021] The titanium oxide particles that exhibit high anti-algae properties are not titanium oxide particles with a copper compound supported on the surface, or a mixture of a copper compound and titanium oxide particles, which are obtained by adding a copper compound to existing titanium oxide particles, but rather titanium oxide particles with copper dissolved therein, which are obtained by adding copper to a titanium compound at a stage before the titanium oxide particles are formed and then forming titanium oxide particles.
[0022] The copper component to be dissolved in the titanium oxide particles may be derived from a simple copper or a copper compound, and may be, for example, a simple copper metal (Cu), an oxide (CuO, Cu2O), a hydroxide, a chloride (CuCl, CuCl2), an iodide (CuI), a bromide (CuBr, CuBr2), a nitrate (Cu(NO3)2), a sulfate (CuSO4), a carbonate (CuCO3), an acetate (Cu(CH3COO)2), a pyrophosphate (Cu2P2O7), a complex compound, or a combination of two or more of these. Among these, it is preferable to use chlorides (CuCl, CuCl2), nitrates (Cu(NO3)2), and sulfates (CuSO4).
[0023] The amount of copper component dissolved in the titanium oxide particles is preferably 2 to 200 in terms of the molar ratio to titanium (Ti / Cu), more preferably 2.5 to 100, and even more preferably 5 to 50. This is because if the molar ratio is less than 2, the titanium oxide content decreases and the anti-algae properties are not fully exhibited, whereas if it exceeds 200, the copper content decreases and the anti-algae properties may be insufficient.
[0024] The titanium oxide particles having copper dissolved therein may further have tin dissolved therein in addition to copper. When tin is dissolved in titanium oxide, rutile titanium oxide can be obtained.
[0025] The titanium oxide particles having copper dissolved therein may further have zinc dissolved therein in addition to copper. When zinc is dissolved in addition to copper, even higher anti-algae properties may be obtained.
[0026] The method for dissolving a different metal in titanium oxide crystal is not particularly limited, but examples include gas phase methods (CVD method, PVD method, etc.), liquid phase methods (hydrothermal method, sol-gel method, etc.), and solid phase methods (high temperature firing method, etc.).
[0027] When tin is dissolved in titanium oxide particles having copper dissolved therein, the tin component may be a tin element or a tin compound, such as a tin metal element (Sn), oxide (SnO, SnO2), hydroxide, chloride (SnCl2, SnCl4), nitrate (Sn(NO3)2), sulfate (SnSO4), halogenide (Br, I) other than chloride, oxoacid salt (Na2SnO3, K2SnO3), complex compound, etc., and one or more of these may be used in combination. Among them, it is preferable to use oxide (SnO, SnO2), chloride (SnCl2, SnCl4), sulfate (SnSO4), and oxoacid salt (Na2SnO3, K2SnO3).
[0028] When tin is further dissolved in titanium oxide particles having copper dissolved therein, the amount of tin component, in terms of the molar ratio with titanium (Ti / Sn), is preferably 1 to 1,000, more preferably 5 to 500, and even more preferably 5 to 100. This is because, if the molar ratio is less than 1, the titanium oxide content decreases and the anti-algae properties are not fully exhibited, whereas if it exceeds 1,000, the conversion to rutile titanium oxide may be insufficient.
[0029] When zinc is dissolved in titanium oxide particles, the zinc component may be zinc alone or derived from a zinc compound, such as zinc metal (Zn), oxide (ZnO), hydroxide, chloride (ZnCl2), nitrate (Zn(NO3)2), sulfate (ZnSO4), halogenides (Br, I) other than chloride, zinc acetate (Zn(CH3COO)2), complex compounds, etc., and one or more of these may be used in combination. Among these, it is preferable to use oxide (ZnO), chloride (ZnCl2), and sulfate (ZnSO4).
[0030] When zinc is further dissolved in the titanium oxide particles, the amount of the zinc component, in terms of the molar ratio with titanium (Ti / Zn), is preferably 2 to 200, more preferably 2.5 to 100, and even more preferably 5 to 50. This is because, if the molar ratio is less than 2, the titanium oxide content decreases and the anti-algae properties are not fully exhibited, whereas if it exceeds 200, the zinc content decreases and the anti-algae properties may be insufficient.
[0031] The titanium oxide particles having copper dissolved therein may be used alone, or may be used in combination of two or more types of titanium oxide particles having different proportions of dissolved copper or titanium oxide particles having other metal components dissolved therein such as tin and zinc in addition to copper. When two or more types having different anti-algae properties are combined, the anti-algae properties may be enhanced.
[0032] <Titanium oxide particles without copper solid solution> Titanium oxide particles with copper dissolved in solid solution have improved anti-algae properties due to the presence of copper in solid solution, but the decomposition activity of other organic matter may decrease. Since a wide variety of dirt exists in the real environment, it is more preferable to use the anti-algae agent of the present invention in combination with titanium oxide particles with copper dissolved in solid solution, which have excellent anti-algae properties, and titanium oxide particles without copper dissolved in solid solution, which have excellent decomposition activity of organic matter. Depending on the combination, the effect of increasing the anti-algae properties and decomposition activity of organic matter may be obtained compared to titanium oxide particles with copper dissolved in solid solution and titanium oxide particles without copper dissolved in solid solution, respectively, alone.
[0033] The titanium oxide particles not having copper dissolved therein are not particularly limited, and titanium oxide particles used as a photocatalyst can be used.
[0034] The crystalline phase of the titanium oxide particles in which copper is not dissolved is preferably mainly anatase type or rutile type. Here, "mainly" means that the titanium oxide particles of this crystalline phase account for 50% by mass or more of the entire titanium oxide particles, preferably 70% by mass or more, more preferably 90% by mass or more, and may be 100% by mass.
[0035] When anatase type titanium oxide particles are selected as titanium oxide particles not having copper dissolved therein, the anti-algae properties tend to be particularly high, while when rutile type titanium oxide particles are selected, the organic matter decomposition activity tends to be particularly high.
[0036] Titanium oxide particles that do not contain dissolved copper can also be used with dissolved tin or with a metal compound such as platinum, gold, palladium, iron, copper, or nickel supported thereon in order to enhance the photocatalytic activity.
[0037] When tin is dissolved in titanium oxide particles not containing copper, the tin component may be derived from a tin element or a tin compound, such as a tin metal element (Sn), oxide (SnO, SnO2), hydroxide, chloride (SnCl2, SnCl4), nitrate (Sn(NO3)2), sulfate (SnSO4), halogenides (Br, I) other than chloride, oxoacid salts (Na2SnO3, K2SnO3), complex compounds, etc., and one or more of these may be used in combination. Among these, it is preferable to use oxides (SnO, SnO2), chlorides (SnCl2, SnCl4), sulfates (SnSO4), and oxoacid salts (Na2SnO3, K2SnO3).
[0038] When tin is dissolved in titanium oxide particles not containing dissolved copper, the amount of tin component is preferably a molar ratio to titanium (Ti / Sn) of 1 to 1,000, more preferably 5 to 500, and even more preferably 5 to 100. This is because, if the molar ratio is less than 1, the titanium oxide content decreases and the anti-algae properties are not fully exhibited, and, if it exceeds 1,000, conversion to rutile titanium oxide may be insufficient.
[0039] The mass ratio of titanium oxide particles containing copper as a solid solution to titanium oxide particles containing no copper as a solid solution [titanium oxide particles containing copper as a solid solution / titanium oxide particles containing no copper as a solid solution] is preferably in the range of 99 to 0.1, more preferably 9 to 0.2, and even more preferably 4 to 0.4. This is because if the mass ratio exceeds 99, the decomposition activity of organic matter becomes insufficient, and if it is less than 0.1, the anti-algae property may become insufficient.
[0040] The titanium oxide particles not having copper dissolved therein may be used alone or in combination of two or more kinds.
[0041] <Dispersion of titanium oxide particles containing copper> The anti-algae agent of the present invention may be one in which titanium oxide particles having copper dissolved therein are dispersed in an aqueous dispersion medium (titanium oxide particle dispersion liquid).
[0042] As the aqueous dispersion medium, water is preferably used, but a mixed solvent of water and a hydrophilic organic solvent mixed with water at any ratio may be used. As the water, for example, purified water such as filtered water, deionized water, distilled water, and pure water is preferable. As the hydrophilic organic solvent, for example, alcohols such as methanol, ethanol, and isopropanol, glycols such as ethylene glycol, and glycol ethers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, and propylene glycol-n-propyl ether are preferable. When a mixed solvent is used, the ratio of the hydrophilic organic solvent in the mixed solvent is preferably more than 0% by mass and 50% by mass or less, more preferably 20% by mass or less, and even more preferably 10% by mass or less.
[0043] The titanium oxide particles in which copper is dissolved in the titanium oxide particle dispersion liquid have a volume-based 50% cumulative distribution diameter (hereinafter referred to as D 50 The thickness of the nanoparticles is preferably 5 to 50 nm, more preferably 5 to 40 nm, and further preferably 5 to 30 nm. 50However, if it is less than 5 nm, the photocatalytic activity may be insufficient, and if it exceeds 50 nm, the dispersion and the photocatalytic film obtained from the dispersion may become opaque.
[0044] In addition, the titanium oxide particles in which copper is dissolved in the titanium oxide particle dispersion liquid have a volume-based 90% cumulative distribution diameter (hereinafter referred to as D 90 The thickness of the film is preferably 5 to 150 nm, and more preferably 5 to 80 nm. 90 However, if it is less than 5 nm, the photocatalytic activity may be insufficient, and if it exceeds 150 nm, the dispersion and the photocatalytic thin film obtained from the dispersion may become opaque.
[0045] In the present invention, the titanium oxide particles in which copper is dissolved in the titanium oxide particle dispersion liquid are D 50 and D. 90 It is preferable that the particles have a molecular weight within the above range, because a dispersion having high photocatalytic activity and high transparency and a photocatalytic film obtained from the dispersion can be obtained.
[0046] In addition, the D of the titanium oxide particles in the titanium oxide particle dispersion liquid 50 and D. 90 As an apparatus for measuring the surface tension, for example, ELSZ-2000ZS (manufactured by Otsuka Electronics Co., Ltd.), NANOTRACK WAVE II (manufactured by Microtrack Bell Co., Ltd.), nanoPartica SZ-100V2 (manufactured by Horiba, Ltd.), etc. can be used.
[0047] The concentration of titanium oxide particles having copper dissolved therein in the titanium oxide particle dispersion is preferably 0.01 to 20 mass %, particularly preferably 0.1 to 10 mass %, from the viewpoint of ease of producing a photocatalytic thin film of a required thickness.
[0048] The concentration of the titanium oxide particle dispersion liquid can be calculated from the mass of the non-volatile matter (titanium oxide particles) after sampling a portion of the titanium oxide particle dispersion liquid and heating it at 105°C for 1 hour to volatilize the solvent, and the mass of the sampled titanium oxide particle dispersion liquid, according to the following formula. Concentration of titanium oxide particle dispersion (%) = [mass of non-volatile matter (g) / mass of titanium oxide particle dispersion (g)] x 100
[0049] The titanium oxide particle dispersion liquid, which is one embodiment of the algae-preventing agent of the present invention, may further contain the titanium oxide particles in which copper is not dissolved. The titanium oxide particles not having copper dissolved therein are not particularly limited, and as described above, titanium oxide particles used as a photocatalyst can be used. Titanium oxide particles that do not contain dissolved copper can also be used with dissolved tin or with a metal compound such as platinum, gold, palladium, iron, copper, or nickel supported thereon in order to enhance the photocatalytic activity.
[0050] The mass ratio of titanium oxide particles containing copper as a solid solution to titanium oxide particles containing no copper as a solid solution in the titanium oxide particle dispersion liquid [titanium oxide particles containing copper as a solid solution / titanium oxide particles containing no copper as a solid solution] is preferably in the range of 99 to 0.1, more preferably 9 to 0.2, and even more preferably 4 to 0.4. This is because if the mass ratio exceeds 99, the decomposition activity of organic matter becomes insufficient, and if it is less than 0.1, the anti-algae property may become insufficient.
[0051] Titanium oxide particles in which copper is not dissolved in the titanium oxide particle dispersion liquid are determined by the volume-based 50% cumulative distribution diameter (hereinafter referred to as D 50 The thickness of the nanoparticles is preferably 5 to 50 nm, more preferably 5 to 40 nm, and further preferably 5 to 30 nm. 50 However, if it is less than 5 nm, the photocatalytic activity may be insufficient, and if it exceeds 50 nm, the dispersion and the photocatalytic film obtained from the dispersion may become opaque.
[0052] In addition, the titanium oxide particles in which copper is not dissolved in the titanium oxide particle dispersion liquid have a volume-based 90% cumulative distribution diameter (hereinafter referred to as D 90 The thickness of the film is preferably 5 to 150 nm, and more preferably 5 to 80 nm. 90 However, if it is less than 5 nm, the photocatalytic activity may be insufficient, and if it exceeds 150 nm, the dispersion and the photocatalytic thin film obtained from the dispersion may become opaque.
[0053] Titanium oxide particles in which copper is not dissolved in the titanium oxide particle dispersion liquid are D 50 and D. 90 It is preferable that the particles have a molecular weight within the above range, because a dispersion having high photocatalytic activity and high transparency and a photocatalytic film obtained from the dispersion can be obtained.
[0054] In addition, when the titanium oxide particle dispersion liquid is a mixed dispersion liquid of titanium oxide particles in which copper is dissolved and titanium oxide particles in which copper is not dissolved, D 50 D is preferably 5 to 50 nm, more preferably 5 to 40 nm, and further preferably 5 to 30 nm. 90 The thickness is preferably 5 to 150 nm, and more preferably 5 to 80 nm.
[0055] In addition, D of titanium oxide particles not containing copper as a solid solution, titanium oxide particles containing copper as a solid solution, and titanium oxide particles containing no copper as a solid solution in the titanium oxide particle dispersion liquid is 50 and D. 90 The apparatus for measuring is as described above.
[0056] The concentration of titanium oxide particles not containing copper in a solid solution in the titanium oxide particle dispersion is preferably 0.01 to 20 mass %, particularly preferably 0.1 to 10 mass %, from the viewpoint of ease of producing a photocatalyst film of a required thickness. In addition, the total concentration of titanium oxide particles containing copper as a solid solution and titanium oxide particles containing no copper as a solid solution in the titanium oxide particle dispersion liquid is also preferably 0.01 to 20 mass %, and particularly preferably 0.1 to 10 mass %, from the viewpoint of ease of producing a photocatalyst film of a required thickness. The method for measuring the concentration of titanium oxide particles in which copper is not dissolved, and the total concentration of titanium oxide particles in which copper is dissolved and titanium oxide particles in which copper is not dissolved in the titanium oxide particle dispersion liquid is the same as the method for measuring the concentration of titanium oxide particles in which copper is dissolved.
[0057] In the titanium oxide particle dispersion liquid, the titanium oxide particles having copper dissolved therein may be used alone or in combination of two or more kinds. When the titanium oxide particle dispersion liquid contains titanium oxide particles having no copper dissolved therein, the titanium oxide particles having no copper dissolved therein may be used alone or in combination of two or more kinds.
[0058] Furthermore, a binder may be added to the titanium oxide particle dispersion liquid, which is one embodiment of the algae-preventing agent of the present invention, for the purpose of facilitating application of the dispersion liquid to the surfaces of various members described below and facilitating adhesion of the particles. Examples of binders include metal compound binders containing silicon, aluminum, titanium, zirconium, etc., and organic resin binders containing fluorine-based resins, acrylic resins, urethane resins, etc.
[0059] The mass ratio of the binder to the titanium oxide particles [titanium oxide particles / binder] is preferably in the range of 99 to 0.01, more preferably 9 to 0.1, and even more preferably 2.5 to 0.4. Here, the "titanium oxide particles" in the mass ratio is based on the mass of "titanium oxide particles with copper dissolved" when the titanium oxide particle dispersion liquid contains only titanium oxide particles with copper dissolved, and based on the total mass of "titanium oxide particles with copper dissolved and titanium oxide particles with copper not dissolved" when the titanium oxide particle dispersion liquid also contains titanium oxide particles with copper not dissolved. This is because when the mass ratio exceeds 99, the adhesion of the titanium oxide particles to the surfaces of various components becomes insufficient, and when it is less than 0.01, the photocatalytic activity may become insufficient.
[0060] Among them, in order to obtain an excellent photocatalytic film having high photocatalytic activity and transparency, it is preferable to add and use a silicon compound-based binder in a mass ratio (titanium oxide / silicon compound-based binder) of 99 to 0.01, more preferably 9 to 0.1, and even more preferably 2.5 to 0.4. Here, the silicon compound-based binder is a colloidal dispersion, solution, or emulsion of a silicon compound containing a solid or liquid silicon compound in an aqueous dispersion medium, and specific examples thereof include colloidal silica (preferably 1 to 150 nm in particle size); silicate solutions such as silicates; silane and siloxane hydrolyzate emulsions; silicone resin emulsions; and emulsions of copolymers of silicone resins and other resins, such as silicone-acrylic resin copolymers and silicone-urethane resin copolymers.
[0061] <Method of manufacturing a dispersion of titanium oxide particles containing copper> The method for producing a dispersion of titanium oxide particles having copper dissolved therein is for obtaining titanium oxide particles having copper dissolved therein in a dispersed state in an aqueous dispersion medium, and includes the following steps (1) and (2):
[0062] (1) A process for producing a copper-containing peroxotitanic acid solution from raw titanium compounds, copper compounds, a basic substance, hydrogen peroxide and an aqueous dispersion medium. (2) A process for heating the copper-containing peroxotitanic acid solution produced in the above process (1) at 80 to 250°C under pressure control to obtain a titanium oxide particle dispersion liquid in which copper is dissolved.
[0063] When the dispersion liquid of titanium oxide particles having copper dissolved therein contains titanium oxide particles having no copper dissolved therein, the method further includes the following steps (3) to (5).
[0064] (3) A process for producing a peroxotitanic acid solution from a raw material titanium compound, a basic substance, hydrogen peroxide, and an aqueous dispersion medium. (4) A process for heating the peroxotitanic acid solution produced in the above process (3) at 80 to 250° C. under pressure control to obtain a titanium oxide particle dispersion liquid. (5) A step of mixing the titanium oxide particle dispersion liquid containing copper in a solid solution obtained in the steps (2) and (4) with the titanium oxide particle dispersion liquid containing no copper in a solid solution.
[0065] Steps (1) and (2) are for producing a titanium oxide particle dispersion liquid containing dissolved copper, steps (3) and (4) are for producing a titanium oxide particle dispersion liquid containing dissolved copper, and step (5) is for mixing the titanium oxide particle dispersion liquid containing dissolved copper obtained in step (2) with the copper-free titanium oxide particle dispersion liquid obtained in step (4) to ultimately produce a titanium oxide particle dispersion liquid containing dissolved copper and a titanium oxide particle dispersion liquid not containing dissolved copper. Each step will be described in detail below.
[0066] ·Process (1): In step (1), a copper-containing peroxotitanic acid solution is produced by reacting starting titanium compound, copper compound, a basic substance and hydrogen peroxide in an aqueous dispersion medium. When tin or zinc is to be dissolved in the solution, a tin compound or a zinc compound may be added to the raw material titanium compound and basic substance.
[0067] The reaction method may be any of the following methods i) to iii). i) A method in which a copper compound is added to and dissolved in a raw material titanium compound and a basic substance in an aqueous dispersion medium, and then copper-containing titanium hydroxide is obtained, impurity ions other than the contained metal ions are removed, and hydrogen peroxide is added to obtain copper-containing peroxotitanic acid. ii) A method in which a basic substance is added to a raw material titanium compound in an aqueous dispersion medium to produce titanium hydroxide, impurity ions other than the contained metal ions are removed, a copper compound is added, and then hydrogen peroxide is added to produce copper-containing peroxotitanic acid. iii) A method in which a basic substance is added to a raw material titanium compound in an aqueous dispersion medium to form titanium hydroxide, impurity ions other than the contained metal ions are removed, hydrogen peroxide is added to form peroxotitanic acid, and a copper compound is then added to form copper-containing peroxotitanic acid.
[0068] In addition, in the first step of method i), the "raw titanium compound and basic substance in an aqueous dispersion medium" may be separated into two aqueous dispersion media, such as an "aqueous dispersion medium in which the raw titanium compound is dispersed" and an "aqueous dispersion medium in which the basic substance is dispersed", and each compound may be dissolved in one or both of the two liquids according to the solubility of the copper compound in the two liquids, and then the two may be mixed.
[0069] After the copper-containing peroxotitanic acid is thus obtained, it is subjected to a hydrothermal reaction in step (2) described below, whereby titanium oxide particles in which copper is dissolved in a solid solution can be obtained.
[0070] Here, examples of the raw titanium compound include inorganic acid salts such as titanium chloride, nitrate, and sulfate, organic acid salts such as formic acid, citric acid, oxalic acid, lactic acid, and glycolic acid, and titanium hydroxide precipitated by hydrolysis of an aqueous solution of these salts with an alkali, and these may be used alone or in combination of two or more. Among these, it is preferable to use titanium chloride (TiCl3, TiCl4).
[0071] The copper compound and the aqueous dispersion medium are used in the above-mentioned proportions. The concentration of the aqueous titanium compound solution formed from the titanium compound and the aqueous dispersion medium is preferably 60% by mass or less, particularly 30% by mass or less. The lower limit of the concentration is appropriately selected, but is usually preferably 1% by mass or more.
[0072] The basic substance is used to convert the raw titanium compound into titanium hydroxide, and examples of the basic substance include hydroxides of alkali metals or alkaline earth metals such as sodium hydroxide and potassium hydroxide, ammonia, alkanolamines, alkylamines, and other amine compounds, of which ammonia is particularly preferred and is added in an amount such that the pH of the aqueous solution of the raw titanium compound becomes 7 or higher, particularly 7 to 10. The basic substance may be used in the form of an aqueous solution of an appropriate concentration together with the aqueous dispersion medium.
[0073] Hydrogen peroxide is used to convert the raw titanium compound or titanium hydroxide into peroxotitanium, i.e., a titanium oxide compound containing Ti-OO-Ti bonds, and is usually used in the form of aqueous hydrogen peroxide. The amount of hydrogen peroxide added is preferably 1.5 to 20 times the molar amount of titanium or the combined amount of titanium and copper. In the reaction of converting the raw titanium compound or titanium hydroxide into peroxotitanic acid by adding hydrogen peroxide, the reaction temperature is preferably 5 to 80°C, and the reaction time is preferably 30 minutes to 24 hours.
[0074] The copper-containing peroxotitanic acid solution thus obtained may contain an alkaline substance or an acidic substance for adjusting the pH, etc. Examples of the alkaline substance include ammonia, sodium hydroxide, calcium hydroxide, alkylamines, etc., and examples of the acidic substance include inorganic acids such as sulfuric acid, nitric acid, hydrochloric acid, carbonic acid, phosphoric acid, etc., and organic acids such as formic acid, citric acid, oxalic acid, lactic acid, glycolic acid, etc. In this case, the pH of the obtained peroxotitanic acid solution is preferably 1 to 9, particularly 4 to 7, from the viewpoint of safety in handling.
[0075] ·Process (2): In step (2), the copper-containing peroxotitanic acid solution obtained in step (1) is subjected to a hydrothermal reaction under pressure control at a temperature of 80 to 250°C, preferably 100 to 250°C, for 0.01 to 24 hours. The reaction temperature is appropriately 80 to 250°C from the viewpoint of reaction efficiency and reaction controllability, and as a result, the copper-containing peroxotitanic acid is converted into titanium oxide particles in which copper is dissolved. Here, "under pressure control" means that when the reaction temperature exceeds the boiling point of the dispersion medium, the reaction temperature is maintained by applying appropriate pressure so that the reaction temperature can be maintained, and includes the case where the reaction temperature is controlled at atmospheric pressure when the temperature is set to a temperature below the boiling point of the dispersion medium. The pressure used here is usually about 0.12 to 4.5 MPa, preferably about 0.15 to 4.5 MPa, and more preferably about 0.20 to 4.5 MPa. The reaction time is preferably 1 minute to 24 hours. By this step (2), a titanium oxide particle dispersion liquid in which copper is dissolved is obtained. The pH of the dispersion liquid of titanium oxide particles having copper dissolved therein obtained in step (2) is preferably 7 to 14, and more preferably 9 to 14. The dispersion liquid of titanium oxide particles having copper dissolved therein obtained in step (2) may contain an alkaline substance or an acidic substance for adjusting the pH or the like so that the pH becomes as described above, and the alkaline substance, acidic substance, and method of adjusting the pH are the same as those for the copper-containing peroxotitanic acid solution obtained in the above-mentioned step (1).
[0076] The particle diameter of the titanium oxide particles obtained here (D 50 and D. 90 ) is preferably in the range as described above, and the particle diameter can be controlled by adjusting the reaction conditions. For example, the particle diameter can be reduced by shortening the reaction time or the temperature rise time.
[0077] ·Process (3): In step (3), a titanium oxide particle dispersion liquid that does not contain copper is produced separately from the above steps (1) and (2). A peroxotitanic acid solution can be obtained in the same manner as in step (1) except that no copper compound is used. When tin is to be dissolved in the titanium compound, a tin compound may be added to the titanium compound as a raw material.
[0078] ·Process (4): In step (4), the peroxotitanic acid solution obtained in step (3) above is subjected to a hydrothermal reaction under pressure control in the same manner as in step (2), thereby obtaining a titanium oxide particle dispersion liquid.
[0079] ·Process (5): In step (5), the titanium oxide particle dispersion liquid in which copper is dissolved obtained in step (2) is mixed with the titanium oxide particle dispersion liquid in which copper is not dissolved obtained in step (4). The mixing method is not particularly limited, and may be a method of stirring with a stirrer or a method of dispersing with an ultrasonic disperser. The temperature during mixing is 20 to 100°C, preferably 20 to 80°C, and more preferably 20 to 40°C, and the time is preferably 1 minute to 3 hours. Regarding the mixing ratio, the titanium oxide particles in which copper is dissolved and the titanium oxide particles in which copper is not dissolved may be mixed at the mass ratio as described above. D measured by dynamic light scattering method using laser light of titanium oxide particles in titanium oxide particle dispersion liquid 50 and D. 90 is as described above. Also, the device for measuring it is as described above.
[0080] The concentration of titanium oxide particles in the titanium oxide particle dispersion thus prepared (each concentration of titanium oxide particles having copper dissolved therein and titanium oxide particles having no copper dissolved therein, and the total concentration of titanium oxide particles having copper dissolved therein and titanium oxide particles having no copper dissolved therein) is preferably 0.01 to 20 mass%, particularly preferably 0.1 to 10 mass%, from the viewpoint of ease of preparation of a photocatalytic film of a required thickness, as described above. Regarding concentration adjustment, if the concentration is higher than the desired concentration, it can be reduced by diluting with an aqueous solvent, and if it is lower than the desired concentration, it can be increased by volatilizing or filtering off the aqueous solvent.
[0081] The concentration of the titanium oxide particle dispersion liquid can be measured by sampling a portion of the titanium oxide particle dispersion liquid, heating it at 105° C. for 3 hours to volatilize the solvent, and calculating the concentration from the mass of the non-volatile content (titanium oxide particles) after heating and the mass of the sampled titanium oxide particle dispersion liquid according to the following formula. Concentration of titanium oxide particle dispersion (%) = [mass of non-volatile matter (g) / mass of titanium oxide particle dispersion (g)] x 100
[0082] In addition, when adding a binder that enhances the above-mentioned film-forming properties, it is preferable to add a solution of the above-mentioned binder (aqueous binder solution) to the titanium oxide particle dispersion liquid whose concentration has been adjusted as described above so that the desired concentration is obtained after mixing.
[0083] <Anti-algae method and member having anti-algae agent on its surface> The algae-preventing agent of the present invention (particularly the titanium oxide particle dispersion liquid) can be used to form a photocatalytic film on the surface of various members. That is, the anti-algae agent of the present invention can be suitably used in a method for preventing algae on the surfaces of various members. A step of applying the anti-algae agent of the present invention (particularly a titanium oxide particle dispersion liquid containing an aqueous dispersion medium) to the surface of a member; and A process to dry the surface of the component to which the anti-algae agent has been applied. and preferably further comprises a step of irradiating the surface of the member with ultraviolet light after the step of drying the surface of the member. Here, the various members are not particularly limited, but examples of the materials for the members include organic materials and inorganic materials. These can have various shapes according to their respective purposes and uses.
[0084] Examples of organic materials include synthetic resin materials such as polyvinyl chloride resin (PVC), polyethylene (PE), polypropylene (PP), polycarbonate (PC), acrylic resin, polyacetal, fluororesin, silicone resin, ethylene-vinyl acetate copolymer (EVA), acrylonitrile-butadiene rubber (NBR), polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polyvinyl butyral (PVB), ethylene-vinyl alcohol copolymer (EVOH), polyimide resin, polyphenylene sulfide (PPS), polyetherimide (PEI), polyetheretherimide (PEEI), polyetheretherketone (PEEK), melamine resin, phenolic resin, acrylonitrile-butadiene-styrene (ABS) resin, natural materials such as natural rubber, or semi-synthetic materials of the above synthetic resin materials and natural materials. These may be commercialized into required shapes and configurations such as films, sheets, fiber materials, fiber products, other molded products, laminates, etc.
[0085] Examples of inorganic materials include non-metallic inorganic materials and metallic inorganic materials. Examples of non-metallic inorganic materials include glass, ceramics, and stone. These may be commercialized in various forms such as tiles, glass, mirrors, walls, and decorative materials. Examples of metallic inorganic materials include cast iron, steel, iron, iron alloys, aluminum, aluminum alloys, nickel, nickel alloys, and zinc die-casting. These may be plated with the metallic inorganic materials, coated with the organic materials, or plated on the surface of the organic materials or non-metallic inorganic materials.
[0086] The anti-algae agent of the present invention (particularly the titanium oxide particle dispersion liquid) is particularly useful for producing a photocatalytic film by applying it to various components made of inorganic substances such as glass and metals, and organic substances such as resins, which are used in environments where anti-algae properties are required, and is useful for producing a transparent photocatalytic film with high anti-algae properties on various components.
[0087] A method for forming a photocatalytic film on the surface of various members may involve coating the surface of the member with a titanium oxide particle dispersion liquid by a known coating method such as spray coating or dip coating, and then drying the surface by a known drying method such as room temperature drying, far-infrared drying, IH drying or hot air drying. The thickness of the photocatalytic film may be selected from a variety of thicknesses, but is usually preferably in the range of 10 nm to 10 μm.
[0088] As a result, a coating (photocatalytic film) of titanium oxide particles having the above-mentioned anti-algae properties is formed on the surface of the component. In this case, if the dispersion contains the binder in the above-mentioned amount, a coating containing titanium oxide particles and the binder is formed on the surface of the component.
[0089] The photocatalytic film formed in this manner is transparent and exhibits excellent anti-algae and photocatalytic properties, particularly in the ultraviolet region (wavelength 10 to 400 nm). Various components on which this photocatalytic film is formed can exhibit anti-algae, anti-mold, self-cleaning, and other effects on the surface of the components due to the anti-algae and photocatalytic properties of the titanium oxide in which copper has been dissolved. Examples of light containing ultraviolet rays (wavelength 10 to 400 nm) include sunlight, fluorescent lamps, incandescent lamps, LEDs, xenon lamps, high-pressure mercury lamps, low-pressure mercury lamps, and metal halide lamps. EXAMPLES
[0090] EXAMPLES The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples. Various evaluations in the present invention were carried out as follows.
[0091] (1) The 50% and 90% cumulative distribution diameters of titanium oxide particles in the liquid (D 50 and D. 90 ) D of titanium oxide particles in liquid 50 and D. 90was calculated as the 50% and 90% cumulative distribution diameters on a volume basis measured by dynamic light scattering using a laser beam. Specifically, the photocatalyst coating liquid was measured using a particle size distribution analyzer (ELSZ-2000ZS, manufactured by Otsuka Electronics Co., Ltd.).
[0092] (2) Identification of the crystalline phase of titanium oxide particles The crystalline phase of the titanium oxide particles was evaluated by powder X-ray diffraction. Specifically, the titanium oxide particle dispersion was dried at 105°C for 3 hours, and the titanium oxide particles were collected and analyzed by powder X-ray diffraction (D2 PHASER, Bruker AXS).
[0093] (3) Anti-algae test of photocatalyst The anti-algae performance of the photocatalyst was evaluated using a test method in accordance with the Japanese Industrial Standard JIS R 1712:2022 "Fine ceramics - Anti-algae test of photocatalytic materials." Various titanium oxide particle dispersions prepared in the Examples or Comparative Examples were applied to a 50 mm square glass substrate so that a photocatalytic film had a thickness of 100 nm, and dried in an oven set at 80°C for 1 hour to obtain an evaluation sample. Using this evaluation sample, the anti-algae activity of the titanium oxide particles was evaluated according to the above-mentioned JIS standard test. A black light fluorescent lamp (FL20S·BLB, manufactured by TOSHIBA) was used as the light source, and ultraviolet light intensity of 0.25 mW / cm was used. 2 The photocatalytic anti-algae activity value was calculated from the photocatalytic anti-algae activity value due to light irradiation. The test results were evaluated according to the following criteria. ·Very good (marked as ◎) ·More than 50% of Rs. ·Good (marked as ○) ···Rs is between 30% and 50% · Defective (marked as ×) · · · Less than 30% of Rs
[0094] (4) Acetaldehyde gas decomposition performance test of photocatalyst The organic matter decomposition performance of the photocatalyst was evaluated by the decomposition reaction of acetaldehyde gas. Each titanium oxide particle dispersion prepared in the Examples or Comparative Examples was spread on one side of an A4 size (210 mm x 297 mm) PET film using a #7 wire bar coater so that the dry mass of titanium oxide particles was about 20 mg to prepare a sample, which was then dried for 1 hour in an oven set at 80°C to obtain an evaluation sample. Using this evaluation sample, the photocatalytic activity of the titanium oxide particles was evaluated by the decomposition reaction of acetaldehyde gas. The evaluation was performed using a batch-type gas decomposition performance evaluation method. Specifically, a sample for evaluation was placed in a 5L stainless steel cell with a quartz glass window, and the cell was filled with acetaldehyde gas with an initial concentration adjusted to 50% humidity, and light was irradiated from a light source installed on the top of the cell. When acetaldehyde gas is decomposed by the photocatalytic action of titanium oxide, the acetaldehyde gas concentration in the cell decreases. Therefore, the strength of the photocatalytic activity can be confirmed by measuring the change in concentration. The acetaldehyde gas concentration was evaluated by measuring the time from the start of light irradiation until the acetaldehyde gas concentration reached 1 ppm or less using a photoacoustic multi-gas monitor (product name "INNOVA1412", manufactured by LumaSense). The shorter the time, the higher the photocatalytic activity, and the longer the time, the lower the photocatalytic activity. A black light fluorescent lamp (FL20S·BLB, manufactured by TOSHIBA) was used as the light source, and the ultraviolet light intensity was 0.25 mW / cm. 2 Irradiation was performed with . The test results were evaluated according to the following criteria. · Very good (marked as ◎) · Reduced to 1 ppm or less within 5 hours Good (marked as ○) Reduced to 1 ppm within 10 hours after 5 hours · Bad (displayed as ×) · · · More than 10 hours have passed until the drop to 1 ppm, or the drop has not reached 1 ppm even after 24 hours.
[0095] (5) Transparency evaluation of photocatalytic film The transparency of the photocatalyst film formed on the PET film in (4) was evaluated by haze measurement. Haze was measured using a haze meter (NDH-5000, manufactured by Nippon Denshoku Industries Co., Ltd.). The test results were evaluated according to the following criteria. ·Good (marked as ○)···The difference in haze value between the PET film with a photocatalytic film on its surface and the blank PET film is 0.3 or less. · Bad (marked as ×) · The difference in haze value between the PET film with photocatalytic film on its surface and the blank PET film exceeds 0.3
[0096] (6) Preparation of Example / Comparative Example Samples [Example 1] <Preparation of titanium oxide particles containing copper as a solid solution> Copper (II) chloride was added and dissolved in a 36% by mass titanium (IV) chloride aqueous solution so that the Ti / Cu (molar ratio) was 5, and this was then diluted 10 times with pure water, after which 10% by mass ammonia water was gradually added to neutralize and hydrolyze the solution, yielding a precipitate of titanium hydroxide containing copper. The pH at this time was 8. The precipitate obtained was deionized by repeatedly adding pure water and decanting it. After this deionization process, 35% by mass hydrogen peroxide water was added to the titanium hydroxide precipitate containing copper so that the H2O2 / (Ti+Cu) (molar ratio) was 15, and the mixture was then stirred at 70°C for 60 minutes to allow the solution to react sufficiently, yielding a green, transparent copper-containing peroxotitanic acid solution (a). A 500 mL autoclave was charged with 400 mL of copper-containing peroxotitanic acid solution (a), which was then hydrothermally treated for 90 minutes at 130°C, and then pure water was added to adjust the concentration, yielding a dispersion (A) of titanium oxide particles in which copper was dissolved (copper-dissolved titanium oxide concentration: 1.0 mass%). When the titanium oxide particles were subjected to powder X-ray diffraction measurement, the only peaks observed were those of anatase-type titanium oxide, indicating that copper was dissolved in titanium oxide.
[0097] [Example 2] <Preparation of titanium oxide particles containing copper as a solid solution> A dispersion liquid (B) of titanium oxide particles having copper dissolved therein (copper-dissolved titanium oxide concentration: 1.0 mass %) was obtained in the same manner as in Example 1, except that copper (II) chloride was added to a 36 mass % aqueous titanium (IV) chloride solution so that the Ti / Cu (molar ratio) was 25. When the titanium oxide particles were subjected to powder X-ray diffraction measurement, the only peak observed was that of anatase-type titanium oxide, indicating that copper was dissolved in titanium oxide.
[0098] [Preparation Example 3] <Preparation of titanium oxide particles containing copper and tin as a solid solution> A dispersion liquid (C) of titanium oxide particles having copper and tin dissolved therein (copper and tin dissolved titanium oxide concentration 1.0 mass %) was obtained in the same manner as in Preparation Example 1, except that copper (II) chloride was added to a 36 mass % aqueous titanium (IV) chloride solution so that the Ti / Cu (molar ratio) was 25 and tin (IV) chloride was added to the aqueous titanium (IV) chloride solution so that the Ti / Sn (molar ratio) was 10. When the titanium oxide particles were subjected to powder X-ray diffraction measurement, the only peak observed was that of rutile-type titanium oxide, indicating that copper and tin were dissolved in the titanium oxide.
[0099] [Preparation Example 4] <Preparation of titanium oxide particles containing copper and zinc as a solid solution> A dispersion liquid (D) of titanium oxide particles having copper and zinc dissolved therein (concentration of copper and zinc dissolved titanium oxide: 1.0 mass %) was obtained in the same manner as in Preparation Example 1, except that copper chloride (II) was added to a 36 mass % aqueous titanium chloride (IV) chloride solution so that the Ti / Cu (molar ratio) was 25 and zinc chloride (II) was added to the aqueous titanium oxide solution so that the Ti / Zn (molar ratio) was 40. When the titanium oxide particles were subjected to powder X-ray diffraction measurement, the only peaks observed were those of anatase type titanium oxide, indicating that copper and zinc were dissolved in the titanium oxide.
[0100] [Preparation Example 5] <Preparation of titanium oxide particles containing copper as a solid solution> A dispersion liquid (E) of titanium oxide particles having copper dissolved therein (concentration of copper-dissolved titanium oxide: 1.0 mass %) was obtained in the same manner as in Preparation Example 1, except that copper (II) chloride was added to a 36 mass % aqueous titanium (IV) chloride solution so that the Ti / Cu (molar ratio) was 60. When the titanium oxide particles were subjected to powder X-ray diffraction measurement, the only peak observed was that of anatase-type titanium oxide, indicating that copper was dissolved in titanium oxide.
[0101] [Preparation Example 6] <Preparation of titanium oxide particles> A dispersion liquid (F) of titanium oxide particles not containing dissolved copper (titanium oxide concentration 1.0 mass%) was obtained in the same manner as in Preparation Example 1, except that copper (II) chloride was not added to the 36 mass% aqueous titanium (IV) chloride solution. When the titanium oxide particles were subjected to powder X-ray diffraction measurement, the peak observed was that of anatase type titanium oxide.
[0102] [Preparation Example 7] <Preparation of titanium oxide particles containing tin as a solid solution> A dispersion liquid (G) of titanium oxide particles without dissolved tin (concentration of tin-dissolved titanium oxide: 1.0% by mass) was obtained in the same manner as in Preparation Example 3, except that copper (II) chloride was not added to the 36% by mass aqueous solution of titanium (IV) chloride. When the titanium oxide particles were subjected to powder X-ray diffraction measurement, the only peak observed was that of rutile-type titanium oxide, indicating that tin was dissolved in titanium oxide.
[0103] [Preparation Example 8] <Preparation of titanium oxide particles carrying a divalent copper compound> Copper (II) chloride was added to the titanium oxide particle dispersion (F) so that the Ti / Cu (molar ratio) was 25, to obtain a copper (II)-supported titanium oxide particle dispersion (H) (copper (II)-supported titanium oxide concentration 1.0 mass %).
[0104] [Preparation Example 9] <Preparation of a mixture of titanium oxide particles containing copper dissolved therein and titanium oxide particles not containing copper dissolved therein> The titanium oxide particle dispersion liquid (A) containing dissolved copper and the titanium oxide particle dispersion liquid (F) containing no dissolved copper were mixed in a 1:1 (mass ratio) to obtain a mixture (I) of titanium oxide particles containing dissolved copper and titanium oxide particles not containing dissolved copper (total concentration of the two types of titanium oxide: 1.0 mass %).
[0105] [Preparation Example 10] <Preparation of a mixture of titanium oxide particles having copper dissolved therein and titanium oxide particles having tin dissolved therein but not copper dissolved therein> Titanium oxide particles (A) containing dissolved copper and titanium oxide particles (G) containing dissolved tin were mixed in a 1:1 (mass ratio) to obtain a mixture (J) of titanium oxide particles containing dissolved copper and titanium oxide particles not containing dissolved copper (total concentration of the two types of titanium oxide: 1.0 mass%).
[0106] [Preparation Example 11] <Preparation of copper(II) oxide> CuO powder (manufactured by Fuji Film Wako Pure Chemical Industries, Ltd.) was added to pure water to a concentration of 1% by mass and dispersed with a stirrer.
[0107] [Preparation Example 12] <Preparation of a mixture of titanium oxide particles and copper(II) oxide> CuO powder (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added to the titanium oxide particle dispersion (F) so that the Ti / Cu (molar ratio) was 25, to obtain a mixture of titanium oxide particles and copper (II) oxide (titanium oxide concentration 1.0 mass %).
[0108] Table 1 shows the molar ratio and dispersed particle diameter (D 50 and D. 90 ) and the crystal phases of titanium oxide particles are shown in the table below.
[0109] [Table 1] (*1) Copper (II) is supported in an amount such that the Ti / Cu (molar ratio) is 25. (*2) Titanium oxide particle dispersion liquid (A): Titanium oxide particle dispersion liquid (F) = 1:1 (mass ratio) (*3) Titanium oxide particle dispersion liquid (A): Titanium oxide particle dispersion liquid (G) = 1:1 (mass ratio) (*4) Copper(II) oxide was added in an amount such that the Ti / Cu (molar ratio) was 25.
[0110] [Example 1] Various evaluations were carried out using the dispersion liquid (A) of titanium oxide particles having copper dissolved therein. The evaluation results of the titanium oxide particles of the present invention are summarized in Table 2 below.
[0111] [Example 2] Various evaluations were carried out using the dispersion liquid (B) of titanium oxide particles having copper dissolved therein.
[0112] [Example 3] Various evaluations were carried out using the dispersion liquid (C) of titanium oxide particles with copper and tin dissolved therein.
[0113] [Example 4] Various evaluations were carried out using the dispersion liquid (D) of titanium oxide particles having copper and zinc dissolved therein.
[0114] [Example 5] Various evaluations were carried out using the dispersion liquid (E) of titanium oxide particles having copper dissolved therein.
[0115] [Example 6] Various evaluations were carried out using a mixture (I) of a dispersion of titanium oxide particles containing copper as a solid solution and titanium oxide particles not containing copper as a solid solution.
[0116] [Example 7] Various evaluations were carried out using a mixture (J) of a dispersion liquid of titanium oxide particles containing copper as a solid solution and titanium oxide particles not containing copper as a solid solution.
[0117] [Example 8] A silicon compound (silica-based) binder (colloidal silica, product name: Snowtex ST-NS, manufactured by Nissan Chemical Industries, Ltd.) was added to the dispersion liquid (A) of titanium oxide particles having copper dissolved therein so that the titanium oxide particles / binder (weight ratio) was 1.5, and the mixture was mixed with a stirrer at 25°C for 10 minutes to obtain a dispersion liquid of titanium oxide particles having copper dissolved therein containing a binder. Various evaluations were carried out using this liquid.
[0118] [Comparative Example 1] Various evaluations were carried out using the dispersion liquid (F) of titanium oxide particles that does not contain copper as a solid solution.
[0119] [Comparative Example 2] Various evaluations were carried out using the dispersion liquid (G) of titanium oxide particles that does not contain copper as a solid solution.
[0120] [Comparative Example 3] Various evaluations were carried out using the dispersion liquid (H) of titanium oxide particles carrying copper.
[0121] [Comparative Example 4] Using the copper oxide dispersion liquid prepared in Preparation Example 11, various evaluations were carried out.
[0122] [Comparative Example 5] Various evaluations were carried out using a mixture of the titanium oxide particle dispersion liquid (F) prepared in Preparation Example 12 and CuO powder.
[0123] [Table 2]
[0124] From the results of the Example and Comparative Examples 1 and 2, it was found that the titanium oxide particles having copper dissolved therein exhibited high anti-algae properties. The results of Example 2 and Comparative Examples 3, 4, and 5 show that copper must be dissolved in the titanium oxide particles in order to exhibit high anti-algae properties.
Claims
1. An anti-algae agent containing titanium oxide particles having copper dissolved therein.
2. 2. The algae control agent according to claim 1, further comprising titanium oxide particles in which copper is not dissolved.
3. An anti-algae agent in which titanium oxide particles having copper dissolved therein are dispersed in an aqueous dispersion medium.
4. 4. The algae-preventing agent according to claim 3, further comprising titanium oxide particles not having copper dissolved therein dispersed in the aqueous dispersion medium.
5. The algae-preventing agent according to claim 3, wherein the dispersed particle diameter of the titanium oxide particles having copper dissolved therein is 5 to 50 nm in terms of 50% cumulative distribution diameter and 5 to 150 nm in terms of 90% cumulative distribution diameter on a volume basis, as measured by a dynamic scattering method using laser light.
6. 4. The algae-preventing agent according to claim 3, wherein the amount of copper dissolved in the titanium oxide particles is 2 to 200 in terms of a molar ratio to titanium (Ti / Cu).
7. A step of applying the anti-algae agent according to any one of claims 3 to 6 to a surface of a member; and A process for drying the surface of components The method for preventing algae on a surface of a member comprises the steps of:
8. The method for preventing algae on a surface of a member according to claim 7, further comprising a step of irradiating the surface of the member with ultraviolet light after the step of drying the surface of the member.
Citation Information
Patent Citations
Photocatalyst material and photocatalyst coating composition
JP2018095797A
Photocatalyst composition, photocatalyst coating film and photocatalyst coating product
JP2018144003A